Water Quality Improvement Using Nature-Based Solutions and its Interlinkages with Sustainable Development Goals - Fonseca Largo, Kalina Marcela; Justus Liebig University Giessen (My University, 2025)
Nature-based solutions (NbS) in aquatic ecosystems catch the attention of policymakers as strategies to directly contribute to Sustainable Development Goal (SDG) 6 and indirectly support other SDGs. However, evidence of their effectiveness is limited. NbS in aquatic ecosystems involve more than addressing water quality issues; they require a clear understanding of their macro-environment. Thus, political, economic, social, technological, environmental, and legal (PESTEL) dimensions significantly influence the success or failure of NbS. To bridge this gap, I developed a multi-method framework that guides the alignment of NbS in crucial aquatic ecosystems within the PESTEL dimensions of developing-country communities. Focusing on Ecuador, rivers, estuaries, lakes, ponds, reservoirs, and riparian zones, which play vital roles as water sources for drinking, irrigation, and fishing in the selected communities, were used to propose NbS. A three-stage framework that integrates a mixed methods approach and involves multi-sectoral stakeholders was employed to shape NbS according to the PESTEL context of the local communities. Artificial floating islands (AFIs), a cost-effective macrophyte-based technology, and passive ecological restoration, a strategy to promote the natural regeneration of headwater vegetation, were evaluated as NbS at different stages. The stages included i) adapting AFIs in local communities by fuzzy cognitive maps, ii) assessing the environmental impacts of passive ecological restoration on páramo communities by remote sensing techniques, water quality assessment, and correlation analysis, and iii) merging AFIs with passive ecological restoration in páramo communities via bibliometric analysis. As a result, in the first stage, multiple PESTEL factors influencing water quality deterioration were identified, along with the potential of AFIs to respond to these challenges. The most influential PESTEL factors recognised were natural water pollutants, human exposure to environmental pollutants, and the violation of environmental legislation in the páramo, mangrove, and rainforest communities, respectively. Moreover, model simulations combining AFIs with strengthening training and education programs, demanding corporate environmental responsibility, and paying for ecosystem services showed an improvement in sustainable water management. In the second and third stages, páramo communities were the focus, including smallholder indigenous and peasants who depend on the páramo for water ecosystem services. Hence, I demonstrated that several PESTEL factors guided by bottom-up (local level) management successfully facilitate passive ecological restoration in páramo communities, maintaining excellent water quality. In contrast, top-down (national level) management overlooks local environmental problems, obstructing passive ecological restoration in páramo to improve water quality. Finally, AFIs and passive ecological restoration were integrated into páramo communities to address several PESTEL challenges related to insufficient funding, tech innovation, community commitment, and land use regulations and to contribute to achieving multiple SDGs. This novel and inclusive framework synthesis of diverse data sources and methodologies provided valuable insights tailored to local realities and adaptable to similar contexts in developing countries.
Keywords: Nature-based solutions (NbS); Aquatic Ecosystems; Sustainable Development Goals (SDG 6); PESTEL analysis; Páramo Ecosystems; ddc:333.7